2022
DOI: 10.1039/d2ob01099b
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of C-alkyl branches to l-iminosugars changes their active site binding orientation

Abstract: L-ido-Deoxynojirimycin (L-ido-DNJ) itself showed no affinity for human lysosomal acid α-glucosidase (GAA), whereas 5-C-methyl-L-ido-DNJ showed a strong affinity for GAA, comparable to the glucose analog DNJ, with a Ki value...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Focusing on the alkyl groups, we noticed that the N -alkyl groups of N -butyl-DAB ( 3f ) and N -(4′-phenylbutyl)-DAB ( 3c ) were accommodated in different pockets. We have previously reported the presence of three pockets of the ligand binding site in the study of 5- C -alkyl-L- ido -DNJ for GAA . It was observed that the alkyl chains of N -butyl-DAB ( 3f ) and N -(4′-phenylbutyl)-DAB ( 3c ) were accommodated in the different pockets in this study as well.…”
Section: Evaluation Of N- or α-1-c-heptyl-dab And -Lab Derivatives As...mentioning
confidence: 99%
See 4 more Smart Citations
“…Focusing on the alkyl groups, we noticed that the N -alkyl groups of N -butyl-DAB ( 3f ) and N -(4′-phenylbutyl)-DAB ( 3c ) were accommodated in different pockets. We have previously reported the presence of three pockets of the ligand binding site in the study of 5- C -alkyl-L- ido -DNJ for GAA . It was observed that the alkyl chains of N -butyl-DAB ( 3f ) and N -(4′-phenylbutyl)-DAB ( 3c ) were accommodated in the different pockets in this study as well.…”
Section: Evaluation Of N- or α-1-c-heptyl-dab And -Lab Derivatives As...mentioning
confidence: 99%
“…We have previously reported the presence of three pockets of the ligand binding site in the study of 5-C-alkyl-Lido-DNJ for GAA. 36 It was observed that the alkyl chains of N-butyl-DAB (3f) and N-(4′-phenylbutyl)-DAB (3c) were accommodated in the different pockets in this study as well. The alkyl chain of N-butyl-DAB (3f) was accommodated in the upper small pocket, while the alkyl chain of N-(4′phenylbutyl)-DAB (3c) was in the lower right pocket (Figure 3B,C).…”
Section: -Lab Derivatives As Glycosidase Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations